2019
DOI: 10.4049/jimmunol.1801337
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of N-Terminal Hinge Glycosylation Enhances Interactions of the Fc Region of Human IgG1 Monomers with Glycan-Dependent Receptors and Blocks Hemagglutination by the Influenza Virus

Abstract: In therapeutic applications in which the Fc of IgG is critically important, the receptor binding and functional properties of the Fc are lost after deglycosylation or removal of the unique Asn 297 N-X-(T/S) sequon. A population of Fcs bearing sialylated glycans has been identified as contributing to this functionality, and high levels of sialylation also lead to longer serum retention times advantageous for therapy. The efficacy of sialylated Fc has generated an incentive to modify the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(58 citation statements)
references
References 78 publications
5
53
0
Order By: Relevance
“…In an earlier study with CHO-K1 cells we demonstrated that a proportion of molecules in which the tailpiece Asn-563 glycan was substituted for alanine ran as multimers in solution when examined by SE-HPLC (24). The loss of the bulky Asn-563 glycan exposes hydrophobic amino acid residues in the tailpiece that facilitate non-covalent interactions in solution.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In an earlier study with CHO-K1 cells we demonstrated that a proportion of molecules in which the tailpiece Asn-563 glycan was substituted for alanine ran as multimers in solution when examined by SE-HPLC (24). The loss of the bulky Asn-563 glycan exposes hydrophobic amino acid residues in the tailpiece that facilitate non-covalent interactions in solution.…”
Section: Resultsmentioning
confidence: 99%
“…(B) The C309L/C575A panel of mutants. Boxed chromatograms represent profiles for equivalent mutants expressed in CHO-K1 cells, as published previously (24).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations